Implementasi Pengaturan Arak Bali Dalam Peraturan Gubernur Bali Nomor 1 Tahun 2020 Tentang Tata Kelola Minuman Fermentasi dan/atau Destilasi Khas Bali - I Wayan Arya Sugiarta; Sri Sulandari; I Nyoman Suargita (Universitas Warmadewa, 2022)
Arak Bali, became a local commodity of Balinese society that has existed for generations. Balinese wine is produced traditionally, distributed locally independently by traditional arak craftsmen. With the affordable price, Balinese wine can be consumed by various groups including children who are still underage. Consumption of Balinese wine is an integral part of Balinese culture, especially in religious ceremonies. The existence of Balinese wine is not only for consumption but has a special role as a means of